(untitled) (American Journal of Islam and Society, 2000)
What does it mean to be a migrant, to be itinerant, to forever engage in a “dialogue of civilization”? How do migrants make sense of their identity in a world where every aspect of it is constantly under negotiation by border-keepers and original settlers and earlier immigrants? In his bold new book Passport Photos, Amitava Kumar, a professor of English at the University of Florida, examines some of the problems faced by diasporic communities through the study of an important document, the passport. To the immigrant, the passport is an important intersection between “identity” and “document.” This deep, sensitive and, at times, funny reading of the passport makes for a very thoughtprovoking book, and I unreserved19 recommend it to anyone who is interested in a sensitive portrayal of the immigrant experience. The book is like immigrants themselves. It speaks in multiple languages, and is obsessed with documents. Among its many tongues, it speaks in academic and political cadences, mixes prose and poetry, sprinkles Urdu and Spanish, quotes Namdeo Dhasal, a poet from India and Louis Arrago, the Mexican poet-activist. It layers Urdu upon Spanish, words upon pictures, and best of all, garnishes it with Kumar’s poetry, which is quite magical. There are several poems, each of which is worth the price of admission on a stand-alone basis. In the second paragraph of its preface, the author makes his point clear: “this book is a forged passport.” There is, of course, a delightful wordplay here. We can read the act of forging as illegal duplication, but we can also read it in terms familiar to a blacksmith, the book is forging or creating a new way to understand passports, borders, being an immigrant and being foreign. As someone who personally knows several “illegal immigrants,” I used their reality as a touchstone to judge the book. If the book speaks to their condition, without romanticizing them or being condescending to them, displaying both their bravery and their baggage, then it is a good book. If the book cannot reach them, it is little more than words and I will dismiss it as yet another piece of desultory identity politicking. The book certainly fulfiils the above criteria, and much more. It represents the multilayered experience of immigrants without reducing it to wordplay. At ...